2019
DOI: 10.2147/ijgm.s197511
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge, awareness, and attitudes about research ethics committees and informed consent among resident doctors</p>

Abstract: Background: Medical research involving humans is now common all over the world. Medical doctors and residents are increasingly involved in such research. As part of their training requirements, medical residents in many institutions have to be involved, to different degrees, in human research projects. Methods: In this study, knowledge, awareness, and attitudes of resident doctors toward research ethics committees (REC) and informed consent (IC) processes were evaluated. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 5 publications
6
18
0
Order By: Relevance
“…These data signify that respondents who handled a greater number of projects exercised and practiced ethical guidelines and attributed high importance to the ethics committee's decision and considered it nal. In our survey, among the trained respondents, 97.7% were aware of the role and functions of the ethics committee, similar results were reported in Jordan and India [21,22]. By contrast, a study from Jordan by Tarboush et al reported that the role of the ethics committee was not well understood by most of their study participants [19].…”
Section: Resultssupporting
confidence: 83%
“…These data signify that respondents who handled a greater number of projects exercised and practiced ethical guidelines and attributed high importance to the ethics committee's decision and considered it nal. In our survey, among the trained respondents, 97.7% were aware of the role and functions of the ethics committee, similar results were reported in Jordan and India [21,22]. By contrast, a study from Jordan by Tarboush et al reported that the role of the ethics committee was not well understood by most of their study participants [19].…”
Section: Resultssupporting
confidence: 83%
“…Moreover, this limited application of proper informed consent processes is in concordance with the fact that graduate students, and even other medical researchers, in developing countries, usually have limited training in research ethics and protection of human subjects during research studies or continuous development/education programs [ 20 , 21 , 22 ]. For example, a study that was conducted in Jordan showed that resident doctors had minimal knowledge of major ethical guidelines such as the Declaration of Helsinki and Belmont Report [ 20 ]. The importance of ethics training in the MENA region to advance scientific research was highlighted in a recent review [ 21 ].…”
Section: Discussionmentioning
confidence: 95%
“…Current results revealed a high appreciation of the respondents to the autonomy of research participants ( Table 2, items 4 & 5). However, specific attitudes toward informed consent ( Table 2, items [11][12][13][14] revealed varying attitudes of respondents in comparison with the published literature [1,[12][13][14][15][16][17]. Specific issues on informed consent are growing rapidly in the field of research ethics; e.g.…”
Section: Discussionmentioning
confidence: 99%